Հայագիտական և տեղեկատու մատենագիտության ենթաբաժնի քարտարանների դերն ու նշանակությունը - Թումասյան, Ռուզաննա (Հայաստանի ազգային գրադարան / National Library of Armenia, 2023)
Thus, Armenian studies and Earth science are of great impor-tance in the preservation, development and transmission of written heritage to the next generations. Bibliographic theories, seminars, discussions and exhibitions are organized on the basis of theoretical knowledge and acquired experience. In the era of modern techno-logical developments, Armenian studies and reference bibliographic works are carried out most effectively. In addition to paper card files, electronic card files and repositories are also of great informational importance, which enable a wide range of readers to use the Arme-nian printed cultural heritage without mediation. It should be added that a number of issues of updating and management of bibliographic and information files related to the digitization of files remain cont-roversial.
Բանբեր Հայաստանի գրադարանների ։ Գիտամեթոդական հանդես ։ Հատուկ թողարկում / Գլխավոր խմբագիր` Աննա Չուլյան ; Պատասխանատու խմբագիր՝ Հայկանուշ Ղազարյան ․- Երևան ։ «Գիրք» հրատարակչություն , 2023 ․- էջ 138 - 142
Keywords: Գրադարանագիտություն, մատենագիտություն և արխիվավարություն